Primary papillary carcinoma in thyroglossal cyst - Saha, Kanu Lal; Datta, Pran Gopal; Datta, Utpal Kumar; Biswas, Ashim Kumar; Begum, Ferdousy (Bangladesh Journal of Otorhinolaryngology, 2011)
Introduction: Thyroglossal cyst is the most common congenital midline neck swelling. Most of the cases are benign with rare malignant transformation is approximately in 1-2% cases. Only about 200 cases have been reported from different centers since 1911. Clinical presentation is similar to that of benign cyst and diagnosis is usually made incidentally during histopathological examination of excised cyst. Case report: We report a case of 46-year-old woman who underwent Sistrunk’s operation for thyroglossal cyst. Histopathological examination revealed papillary carcinoma. Thyroxine was added in suppressive dose and patient was on regular follow-up for 2 years. No thyroid abnormality was found preoperative cytology, scintigraphy as well as per-operative procedure and post-operative follow-up period. Conclusion: Sistrunk’s operation followed by suppressive dose of thyroxin and regular follow up is recommended for thyroglossal duct cyst carcinoma in asymptomatic incidental case without the cyst wall invasion. Key words: Thyroglossal cyst; papillary carcinoma; Sistrunk’s operation. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8855 BJO 2011; 17(2): 135-138